2007
DOI: 10.1055/s-2007-967753
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cosmetic Eyelid Surgery Complications

Abstract: There is a broad spectrum of complications that can occur following cosmetic eyelid surgery. The experienced eyelid surgeon should be able to avoid most serious complications through proper patient selection, a comprehensive preoperative assessment and surgical plan, meticulous surgical technique, and appropriate postoperative care. The aesthetic eyelid surgeon must counsel a patient contemplating blepharoplasty surgery regarding typical expectations including edema, eyelid numbness, dry eyes, and mild blurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 85 publications
(108 reference statements)
2
22
0
Order By: Relevance
“…2 There have been limited reports of methicillin-resistant S aureus infection involving the ocular region, but the rate of infection of this type is hypothesized to be increasing. 3 In general surgery, the value of antibiotic prophylaxis is well-established. Bowater et al 4 found antibiotic prophylaxis to be an effective intervention for preventing postoperative wound infections in a meta-analysis involving 250 clinical trials in over 23 different types of surgery.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…2 There have been limited reports of methicillin-resistant S aureus infection involving the ocular region, but the rate of infection of this type is hypothesized to be increasing. 3 In general surgery, the value of antibiotic prophylaxis is well-established. Bowater et al 4 found antibiotic prophylaxis to be an effective intervention for preventing postoperative wound infections in a meta-analysis involving 250 clinical trials in over 23 different types of surgery.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The rate of postsurgical orbital hemorrhage in this setting is estimated to be 0.05%, with permanent vision loss estimated at 0.01%. 3 Vision loss due to postseptal orbital cellulitis is also of concern.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Despite double-eyelid plasty, levator aponeurotic surgery, eyebrow lifting, epicanthoplasty, and lateral canthoplasty, some East Asian patients are often dissatisfied with their outcomes and request further surgery; they desire less of a small, slanted look and a more refreshed, open, larger vertical palpebral aperture, particularly in the lateral half. 21 Often, this dissatisfaction is caused by lower eyelid descent with aging or as an unwanted complication after blepharoplastyan increased scleral show and widened palpebral fissure Fig. 7 Step-by-step anterior views of the lowering the lower eyelid procedure.…”
Section: Vertical Lower Vector Lengtheningmentioning
confidence: 99%
“…The main causes of lagophthalmos are facial nerve palsy, trauma, eyelid surgery, senile ectropion, and Graves’ ophthalmopathy. An incomplete blink and lagophthalmos frequently occur after upper eyelid ptosis correction, and occur less often following upper and lower blepharoplasty surgery 2. One of the goals when treating lagophthalmos is to prevent exposure keratitis.…”
Section: Introductionmentioning
confidence: 99%